Evaluation of Performance and Potential Clinical Impact of ProSpecT Shiga Toxin Escherichia coli Microplate Assay for Detection of Shiga Toxin-Producing E. coli in Stool Samples - Gavin, Patrick J. (American Society for Microbiology, 2004)
Shiga toxin-producing Escherichia coli bacteria (STEC) are emerging pathogens capable of producing sporadic and epidemic diarrhea, hemorrhagic colitis, and potentially life-threatening hemolytic-uremic syndrome. Although the presence of E. coli O157 can be readily detected in stool by sorbitol-MacConkey agar culture (SMAC), STEC non-O157 serotypes cannot. In contrast to culture, testing for the presence of Shiga toxins 1 and 2 in stool detects both O157 and non-O157 STEC serotypes capable of causing disease. Over two consecutive summers, we evaluated the performance of the ProSpecT Shiga toxin E. coli Microplate assay (Alexon-Trend, Ramsey, Minn.), an enzyme immunoassay for the detection of Shiga toxins 1 and 2, on all stools submitted for culture of enteric pathogens, and the potential clinical impact of Shiga toxin detection. Twenty-nine stool specimens were STEC positive by ProSpecT assay. Twenty-seven of 29 STEC-positive isolates were confirmed by SMAC and serotyping or by a second enzyme immunoassay and PCR (positive predictive value, 93%). Thirteen of 27 confirmed Shiga toxin-producing strains were serotype O157. The remaining 14 strains represented 8 other serotypes. The ProSpecT assay was 100% sensitive and specific for detection of E. coli O157 in stool (7 of 7) compared to SMAC. In addition, the ProSpecT assay detected twice as many STEC as SMAC. Fifty-two percent of confirmed STEC-positive stools were nonbloody. Thus, in our population, screening strategies that test only visibly bloody stools for STEC would miss a majority of cases. Eleven (41%) STEC-positive patients were hospitalized, and eight (30%) developed severe disease (two developed hemolytic-uremic syndrome, and six developed hemorrhagic colitis). Prior to detection of STEC infection, seven (26%) and eight patients (30%) underwent unnecessary diagnostic procedures or received potentially deleterious empirical treatment, respectively. We propose that establishing a specific diagnosis of STEC may have prevented these potentially harmful interventions. We conclude that the ProSpecT assay is sensitive and specific for the detection of Shiga toxins 1 and 2 in stool and has potentially significant clinical impact for the individual patient and public health. Shiga toxin assays should be considered for routine use in settings where prevalence of STEC disease warrants testing.